Partial cricotracheal resection for treatment of subglottic stenosis: complications and outcomes - Meulemans, Jeroen; Mouqni, Laila; Ostyn, Noah; Di Santo, Davide; Hens, Greet; Vander Poorten, Vincent; Dooms, Christophe; De Crem, Nico; De Leyn, Paul; Goeleven, Ann; Delaere, Pierre (Frontiers in Surgery, 2025)
PurposeSubglottic stenosis (SGS) is defined as an obstruction of the subglottic area, potentially extending towards the first tracheal rings. Although endoscopic procedures are frequently preferred as first-line treatment, (partial) cricotracheal resection (PCTR) offers the most durable results. This study aims at reporting and analysing complications and respiratory and vocal outcomes after PCTR.MethodsFor this retrospective cohort analysis, the files of 37 patients with SGS who underwent PCTR in a tertiary referral center were reviewed. Patient- and stenosis-characteristics along with postoperative outcomes and complications were analyzed using descriptive statistics.ResultsThe majority of patients were female (95%), which reflects the high incidence of idiopathic SGS in our patient group (89.2% vs. 2.7% postintubation SGS and 8.1% SGS related to systemic inflammatory disease). Most patients presented with a Cotton grade II (35.1%) and III (54.1%) stenosis, with a mean craniocaudal stenosis length of 17.5 mm. The vast majority of patients (89.2%) had undergone previous endoscopic procedures. The most common complication after PCTR was fibrin deposit/granulation tissue formation at the anastomotic site (n = 15, 40.5%). Other complications were rare, with anastomotic dehiscence, postoperative haemorrhage and vocal cord paralysis each in 1 patient (2.7%), temporary tracheostomy in 2 patients (5.4%), and postoperative wound infection in 3 patients (8.1%). During follow-up, only 2 patients (5.4%) developed restenosis which was successfully salvaged by endoscopic procedures. No patients were long-term tracheostomy dependent. Post-operative mean peak expiratory flow (PEF) percentage showed a 43.7% increase compared to pre-operative. For the mean increase in maximum inspiratory flow (MIF) at 50% this was 1.3 L/s. VHI (voice handicap index) scores increased significantly from baseline preoperative score of 27.5 (±23.7) to a mean value of 54.9 (±18.7) (p = 0.002) 1-month postoperatively but decreased below preoperative scores after 2 years (22.2 ± 18.1, p = 0.036).ConclusionPCTR is an efficient treatment for SGS, with low complication rates, a low rate of long-term restenosis and good vocal outcomes.